A PERANCANGAN ALAT BANTU (JIG) DIGITAL CALIPER UNTUK MENGUKUR KEDALAMAN YANG LEBIH AKURAT DI CV. HAHAN ACINTYA - Pujosakti Herdhianto (Fakultas Sains, Teknologi dan Kesehatan Universitas Sahid Surakarta, 2026)
The potential for measurement errors in workpieces can increase product defects or rejects, which can impact business profits at CV. Hahan Acintya. Therefore, a more accurate digital caliper measuring tool was designed to reduce the number of product defects using the DFSS (Design for Six Sigma) method. This study used the DFSS method with the DMADV procedure, which includes the stages of Define, Measuring, Analyze, Design, and Verify. In the Define stage, Critical to Quality (CTQ) is identified and defect types are classified using a pareto diagram. The Measure stage calculates the DPU, DPO, and DPMO values ​​to determine the initial sigma level. In the Analyze stage, the most common defects are analyzed from the pareto diagram and then problem-solving is developed using a fishbone diagram, which is dominated by worker measurement errors. The Design stage produces a jig design using Solidworks software that can minimize product defects caused by measurement errors. The Verify stage tests the jig implementation in the field and re-measures the defect level and sigma values. The results of the study showed that before and after the implementation of the jig caliper, the sigma level value decreased from 4.39 to 4.65, and the percentage of out-of-tolerance defects decreased from 1.82% to 0%. This proves that the designed jig effectively reduces measurement variation and improves product quality. The conclusion from this design is that the jig caliper addresses the problem of production defects at CV. Hahan Acintya regarding out-of-tolerance defects. This tool assists production workers in measuring the depth of workpieces. In general, there are significant results related to the problem of defects caused by out-of-tolerance.